Phylogenetic and morphological evidence for four new species of Russula (Russulaceae, Basidiomycota) from northwestern China - Song, Yu; Wang, Yu-Yu; Yu, Jin-Ling; Yuan, Rui; Li, Fang (European Journal of Taxonomy, 2024)
Four novel species of subgenus Russula crown clade collected from northwestern China are described based on morphological and phylogenetic evidence. Morphologically, R. griseorosea Y.Song sp. nov. (subsection Puellarinae) is characterized by its brown pileus with a grayish pink tint, basidiospores with warts often connected by fine lines, orthochromatic pileipellis with long terminal cells and septate pileocystidia; R. micangshanensis Y.Song sp. nov. (subsection Olivaceinae) is diagnosed by its large basidia, hymenial cystidia and basidiospores, and spore ornamentations with unequal crests and often twinned warts, which give the spore distinctive appearance; R. minirosea Y.Song sp. nov. (subsection Laricinae) has very small basidiocarp with pileus less than 3.3 cm in diameter, basidiospores with fine reticulum, small basidia, and septate pileocystidia; R. purpureomarginalis F.Li & Y.Song sp. nov. (subsection Xerampelinae) has large basidiospores with often isolated ornamentations, slim basidia and often septate flexuous pileocystidia. Differences between the four novel species and their closely related taxa were analyzed. Phylogenetic analyses based on both ITS and multi-locus (LSU, rpb2 and tef1) were carried out to confirm the distinct taxonomic status of the four novel species.